The Changes of Social Culture and The Level of Migrant Welfare Batak Who Worked in The Informal Sector in Bogor - Habibi Siregar, Fuad; A. Kinseng, Rilus (Sodality: Jurnal Sosiologi Pedesaan, 2015)
The purpose of this research is to analyze the changes of social culture and the level of migrant welfare Batak who worked in the informal sector in the city of Bogor. This research provides a combination of qualitative and quantitative approaches. The qualitative approach is obtained from the results of the indepth interviews. Quantitative survey method using approaches that take the 35 respondents. There is no society which does not suffer changes Migrant Batak is no exception. Changes that occur on the migrants include Batak culture and social change in the level of well-being. Social change include the interactions he does as well as relations with his family before and after becoming migrants. Culture change includes the values of religion, customs and mindset towards material and individualist attitudes. The welfare changes include income levels, access to medical services as well as housing conditions and ownership of the valuables owned by migrant Batak before and after become migrants in the informal sector. Keywords: changes, social structures and cultural structures, the level of migrant welfare